Shadowed Fading in Indoor Off-Body Communication Channels: A Statistical Characterization Using the κ - μ /Gamma Composite Fading Model - Seong Ki Yoo; Cotton, Simon L.; Sofotasios, Paschalis C.; Freear, Steven (IEEE transactions on wireless communications, 2016)
This paper investigates the characteristics of the shadowed fading observed in off-body communications channels at 5.8 GHz. This is realized with the aid of the κ-μ/gamma composite fading model, which assumes that the transmitted signal undergoes κ-μ fading, which is subject to multiplicative shadowing. Based on this, the total power of the multipath components, including both the dominant and scattered components, is subject to non-negligible variations that follow the gamma distribution. For this model, we present an integral form of the probability density function (PDF) as well as important analytic expressions for the PDF, cumulative distribution function, moments, and moment generating function. In the case of indoor off-body communications, the corresponding measurements were carried out in the context of four explicit individual scenarios, namely: line of sight (LOS), non-LOS walking, rotational, and random movements. The measurements were repeated within three different indoor environments and considered three different hypothetical body worn node locations. With the aid of these results, the parameters for the κ-μ/gamma composite fading model were estimated and analyzed extensively. Interestingly, for the majority of the indoor environments and movement scenarios, the parameter estimates suggested that dominant signal components existed even when the direct signal path was obscured by the test subject's body. In addition, it is shown that the κ-μ/gamma composite fading model provides an adequate fit to the fading effects involved in off-body communications channels. Using the Kullback-Leibler divergence, we have also compared our results with another recently proposed shadowed fading model, namely, the κ-μ/lognormal LOS shadowed fading model. It was found that the κ-μ/gamma composite fading model provided a better fit for the majority of the scenarios considered in this paper.